Visual Outcome after Scleral Fixation of Intraocular Lens (SFIOL) Implantation Following Pars Plana Vitrectomy (PPV) and Removal of dropped Intra-Ocular Lens (IOL) (Journal of National Institute of Ophthalmology, 2022)
Introduction: Placement of a posterior chamber scleral fixated intraocular lens (SF-IOL) is the only option for patients whose eyes lack zonular or capsular support. Long-term data comparing the various techniques used to place scleral fixation intraocular lens (SF-IOL) will be crucial to identify optimal strategies for scleral fixation intraocular lens (SF-IOL) implantation.Aim of the study: The aim of the study was to observe the visual outcome after SFIOL implantation following PPV in case of dropped intraocular lens.Methods: This prospective observational study was conducted at National Institute of Ophthalmology & Hospital, Dhaka, Bangladesh. The study duration was 6 months, from August 2019 to January 2020. The study was conducted with a total of 30 patients with aphakia due to dropped intraocular lenses. The patients were selected non-randomly on a first come first serve basis.Results: The mean age of the participants was 57.7±7.64 years and the majority (60.0%) were female with 66.67% had left eye involvement. Mean visual acuity at baseline was 1.34 ± 0.26 (SD) in the Log MAR unit, which had significant improvement at each follow-up period. After 3 months visual improvement was 0.34±0.27 in LogMAR unit. A few cases of corneal edema, raised intraocular pressure, lens decentration and some other complications were observed after surgery.Conclusion: In most cases, a decent optical outcome may be reached by using this surgical approach. To prove that it might be a safe and effective treatment without zonular or capsular support, long-term follow-up, a large sample size, and many surgeons' involvement are required.J. Natl. Inst. Ophthalmol. 2022;5(1):27-31